PENATALAKSANAAN RESESI GINGIVA DENGAN MENGGUNAKAN GINGIVA BUATAN: MANAGEMENT OF GINGIVAL RECESSION WITH THE USE OF ARTIFICIAL GINGIVA - Eka Fitria Augustina (TALENTA, 2011)
The prevalence, extent, and severity of gingival recession increase with age and more prevalent in males. Recession is an exposure of the root surface and an apical shift of the gingival position. Recession may be localized in one tooth or a number of teeth, or it may be generalized through out the mouth. Gingival recession will be a problem when patient complained about esthetic, because teeth are seen longer . Gingival recession could happen either physiologic or pathologic. Physiologically, it usually increases with age. Pathologically, it is caused by fault tooth brushing technique, malposition, gingival inflammation, abnormal frenum attachment, and iatrogenic dentistry. Treatment of gingival recession result on esthetic problem and pain because of open dentine. Treatment could be done either with surgery or non surgery. Surgery technique can use flap non reposiotion. In this case report, patient had recession in man dible anterior region. She wanted to get esthetic appearance but she did not want to have surgery treatment. Artificial gingival was performend to cover the recession. Material of the artificial gingival is a soft liner ( chairside vinyl polysiloxane resilient denture liner ), because of good biocompatibility, nice colour and texture is invitiate real gingiva, although it has to take it off when eating and cleaning up . Main function of artificial gingival is esthetic function and cover the recession. In conclusion, after treatment showed good esthetic and patient. Beside treatment, we need to suggest patients to do plaque control and visit dentist at least twice a year.